Evolutions of Employment and Turnover in Services in EU - Zaharia, Marian; Enachescu, Daniela; Balacescu, Aniela (Industrija, 2014)
Since the mid-twentieth century services have become a vital economic sector of modern economies. Creating and EU enlargement has boosted strong so-called third sector. Although the general trend in the EU is the convergence, different levels of development and economic crisis of recent years have led to various developments in this sector. This paper presents an analysis of the evolution of services both in the EU and some member states such as Romania, in terms of turnover indices in services and labor input in services during 2003-2012. It also analyzes the correlations between the changes in turnover and the changes in number of employees in this sector.